Optimasi Formula Serum Wajah Menggunakan Ekstrak Etanol Daun Kelor (Moringa oleifera L.) sebagai Pelembap Kulit: Optimization of Face Serum Formula Using Ethanol Extract from Kelor Leaves (Moringa oleifera L.) as a Skin Moisturizer - Elinda Rahayu; Saraswati Ramadhani Priyono (Jurnal Farmasi dan Farmakoinformatika, 2025)
Moringa (Moringa oleifera L.) is a member of the Moringaceae family that is rich in flavonoids and phenolics, especially in the leaves, with potential as an antioxidant and skin moisturizer. Serum is a preparation made with low viscosity so that it can deliver a thin film of active substances to the skin surface and has a high water content so that it can hydrate the skin. This study aims to optimize the formula of a face serum based on ethanol extract of moringa leaves. The extract was obtained using the maceration method and tested at concentrations of 2%, 4%, and 6%. The highest antioxidant activity was shown at a concentration of 6%, which was used as the optimal concentration in formulations with variations of 5%, 10%, and 15% glycerin. Antioxidant activity was tested in vitro using the DPPH method with UV-Vis spectrophotometry, while skin moisture was tested using a moisture skin analyzer. The results showed that all formulations met physical quality standards and had moderate to strong antioxidant activity with IC₅₀ values of F0 (36,772 ppm), F1 (26,966 ppm), F2 (25,300 ppm), and F3 (23,591 ppm). Increased concentrations of extract and glycerin were associated with decreased IC₅₀ values and increased moisturizing effects, with formula 4 producing the most optimal performance.